Erroneous Expert Judgments - Bauer, Henry (Journal of Scientific Exploration, 2012)
<!--[if gte mso 9]> Normal 0 ‘“ ’” MicrosoftInternetExplorer4 <![endif][if !mso]> <mce:style><! st1\:*{behavior:url(#ieooui) } --> <!--[endif][if gte mso 10]--> <!-- /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman";} --> <!--[endif] --> The Editorial in JSE 26:1 suggests the need for a scientific analogue of Slonimsky’s one on erroneous and intemperate judgments in music (Lexicon of Musical Invective: Critical Assaults on Composers Since Beethoven’s Time). Something like that is already available in Cerf and Navasky’s The Experts Speak: The Definitive Compendium of Authoritative Misinformation (1984/1998) and Mission Accomplished! Or How We Won the War in Iraq: The Experts Speak (2008). Highly enjoyable.